2013
DOI: 10.1002/cncr.28417
|View full text |Cite
|
Sign up to set email alerts
|

Racial parities in outcomes after radiotherapy for head and neck cancer

Abstract: Background Although blacks experience worse outcomes after treatment for squamous cell carcinoma of the head and neck (HNSCC), these conclusions were based on populations where blacks comprised a minority of patients. Here, we determined the impact of race on outcomes in HNSCC patients treated with radiotherapy at an institution where blacks comprise the majority of patients. Methods We performed a retrospective cohort study by reviewing 366 black and 236 white patients with non-metastatic HNSCC treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Additionally, the comparative efficacy and toxicity of platinum chemotherapy versus epidermal growth factor receptor (EGFR) inhibitors, namely cetuximab, as radiosensitizers remains an area of great interest currently being studied in the RTOG 1016 and TROG 12.01 trials. Lastly, the low level of HPV-positivity in this study, which is consistent with prior results from our institution [30], limits the generalizability of our results to populations with higher proportions of HPV-positivity.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, the comparative efficacy and toxicity of platinum chemotherapy versus epidermal growth factor receptor (EGFR) inhibitors, namely cetuximab, as radiosensitizers remains an area of great interest currently being studied in the RTOG 1016 and TROG 12.01 trials. Lastly, the low level of HPV-positivity in this study, which is consistent with prior results from our institution [30], limits the generalizability of our results to populations with higher proportions of HPV-positivity.…”
Section: Discussionsupporting
confidence: 80%
“…Hypotheses as to why African American patients do not receive appropriate treatment include late stage of diagnosis, lack of access to care, lack of continual care, poor communication between patient and provider, and patient misconceptions about healthcare [22,28,29]. Furthermore, recent literature examining patients undergoing radiotherapy treatment suggests that disparities in HNC survival can be overcome through increased treatment compliance [30]. These hypotheses should be examined in further detail in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…[24][25][26] The data from The Cancer Genome Atlas study showed that HPV-associated tumors are dominated by PIK3CA mutations (56%), novel alterations involving loss of TRAF3 and amplification of the cell cycle gene E2F1. [9][10][11][12]27 Therefore, this is the first study to pilot test whether there were racial/ethnic differences in mutation profiles that may contribute to disparities in HNSCC prognosis. However, most of these studies were performed mainly in non-Hispanic whites; racial/ethnic differences in HNSCC mutation profiles and prognosis have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite advances in treatments, the 5-year survival rates for HNSCC have not improved for the past 20 years. [7][8][9][10][11] Racial and socioeconomic factors continue to play critical roles in late-stage diagnosis, healthcare access, and poorer clinical outcomes. 6 HNSCC has divergent clinical outcomes among different racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%